Administration of waqf in Malaysia (with special reference to the state of Johore, Malacca, Penang and Selangor) / Nur Humairrah Abdul Rahman…[et al.] - Abdul Rahman, Nur Humairrah; Mohd Sabri, Nur Aishah; Rosly, Nur Sri Soleha; Nooh, Nur Ezzati (2005)
The fundamental aim of this study is to examine whether the administration of waqf in Malaysia have been systemized with reference to four states in Malaysia, namely, Johore, Malacca, Selangor and Penang, well as some comparisons to the administration of waqf in Pakistan. We have done a study based o n interpretation of relevant s tatutes a s well as enactments on relevant states mentioned above. Interview have been conducted in order to obtain different views namely on the point of view legal scholars and Islamic Scholars. By this research we hope to increase awareness among the public regarding the institution of waqf.